Legal Certainty in the Criminalization of Directors Misusing Corporate Social Responsibility (CSR) Funds - Ade Irma Suryani; I Gede Widhiana Suarda; Y. A Triana Ohoiwutun (Rechtenstudent, 2025)
Corporate Social Responsibility (CSR) is a legal obligation for companies as regulated in Article 74 of Law No. 40 of 2007 concerning Limited Liability Companies (PT Law). However, in practice, misuse of CSR funds remains common in both private companies and State-Owned Enterprises (BUMN), creating adverse impacts on society and the government. This study aims to examine the legal framework governing the criminal liability of directors for the misuse of CSR funds within the Indonesian criminal law system and to analyze the application of the principle of legal certainty. Using a normative juridical method with statutory, conceptual, and case approaches, the study finds that directors may be held criminally liable under Article 488 of the Criminal Code when CSR funds are misused in private companies, while similar acts in BUMN may be categorized as corruption under Articles 2 and 3 of the Corruption Law. Nonetheless, ambiguity within Article 74 of the PT Law continues to generate multiple interpretations, potentially hindering legal enforcement and conflicting with the principles of legality and legal certainty. Therefore, a specific regulation (lex specialis) addressing directors’ criminal liability in CSR fund management is required to enhance legal certainty and strengthen accountable and transparent corporate governance.